A Note on Revealed Preference and the Transitivity Condition - Corlett, W. J.; Newman, P. K. (Review of Economic Studies, 1952)
Journal Article A Note on Revealed Preference and the Transitivity Condition Get access W. J. Corlett, W. J. Corlett London Search for other works by this author on: Oxford Academic Google Scholar P. K. Newman P. K. Newman Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 2, 1952, Pages 156–158, https://doi.org/10.2307/2295850 Published: 01 January 1952